The Ethyl Acetate Fraction of Torbangun (Coleus amboinicus L.) Leaves Increasing Milk Production With Up-Regulated Genes Expression of Prolactin Receptor - Ade Chandra Iwansyah; Rizal Martua Damanik; Lilik Kustiyah; Muhammad Hanafi (Journal of Tropical Life Science, 2019)
This study aim was to determine lactagogue effect of torbangun leaves to plasma levels of lactogenic hormone and gene expression of their receptors in mammary glands of lactation rats. Lactagogue activity was evaluated by volume of milk was produced by the rats treated with commercial milk booster contained ‘katuk' leaves extract (AF), ethyl acetate fraction of torbangun leaves (EA), water extraction of torbangun leaves (AQ) and kaempferol (KP). Lactating rats (n=5) of Sprague dawley with six pups were fed with AF, EA, AQ, and KP in the amount of 50 mg/kg, 30 mg/kg, 80 mg/kg and 60 mg/kg body weight, respectively. The feed was given orally every two days and starting from day 2 after giving birth until day 28. The volume of milk was estimated by the increment pup weight after breastfed. The levels of serum lactogenic hormones were determined by ELISA methods. Moreover, in order to measure the gene expression of the lactogenic hormone's receptors in the mammary gland a real time - reverse transcription polymerase chain reaction (RT-PCR) method was performed. The results showed that ethyl acetate fraction of torbangun leaves (EA) (a) was not significantly stimulating the synthesis of serum prolactin and estradiol at day 14 and day 28 lactation period, (b) down-regulated the gene expression of estradiol receptor (ERα) at day 28, and (c) up-regulated the gene expression of prolactin receptor (PRLR) in mammary gland at day 14 and day 28. This study indicated that ethyl acetate fraction of torbangun leaves was induced milk production, within up-regulated the gene expression of prolactin receptor (PRLR) in the mammary gland of lactation rats.